IL-2 regulation of soluble IL-2 receptor levels following thermal injury. - Teodorczyk-Injeyan, J A (1992)
In the immunosuppressed burn patient serum levels of both IL-2 and a soluble form of IL-2 receptor alpha (sIL-2R alpha) are significantly elevated. Strikingly, the production of these markers by the in vitro activated patients' cells is decreased. This study examines the role of IL-2 in the decreased production of the sIL-2R alpha in vitro in patients with major burns (n = 18, 30 to greater than 70% total body surface area). Peripheral blood mononuclear cell (PBMC) cultures from patients with highly elevated serum sIL-2R alpha, and from healthy controls (n = 12) were activated with concanavalin A (Con A) at initiation. In patients' cultures mitogen-induced increments of sIL-2R alpha levels were significantly lower. There was a significant negative correlation (r = 0.64, P less than 0.001) between a high serum sIL-2R alpha level and a decreased lectin-induced sIL-2R alpha release in vitro. Low levels of sIL-2R alpha in patients' samples were not normalized by increasing the number of T lymphocytes. Also exogenous rIL-1 was without effect, whereas rIL-3 increased sIL-2R alpha release in some cultures. However, sIL-2R alpha levels were significantly increased in patients' cultures by (i) addition of exogenous IL-2; (ii) removal of adherent cells; (iii) addition of cyclooxygenase inhibitor, indomethacin; (iv) bypassing cell surface activation by the combination of the calcium ionophore A23187 and the phorbol ester 12-o-tetradecanoyl acetate. The cyclic AMP-elevating drug, forskolin, abrogated the ability of exogenous IL-2 to increase sIL-2R alpha production. Thus, in the burn patient, the reduced in vitro sIL-2R alpha release appears to relate to abnormalities in IL-2 production and action mediated through its functional surface receptor. Elevated levels of sIL-2R alpha in vivo may, therefore, reflect systemic activation of T lymphocytes in response to biologically active IL-2.